Li 9 Na 3 Cs 2 (SO 4 ) 7 Compound, nonlinear optical crystal and its preparation method and use
By developing Li9Na3Cs2(SO4)7 nonlinear optical crystal, the problems of deliques and layered growth habits of existing ultraviolet nonlinear optical crystals have been solved, and the stability and nonlinear optical effects have been improved. It is suitable for a variety of high-tech fields. Nonlinear optics.
Patent Information
- Application Number
- CN202211408077.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-10
AI Technical Summary
Existing ultraviolet nonlinear optical crystals, such as β-BaB2O4, LiB3O5 and K2Be2BO3F2, have problems such as deliques, layered growth habits and difficulty in obtaining large c-direction thicknesses, which limit their application in the ultraviolet band.
A Li9Na3Cs2(SO4)7 nonlinear optical crystal was developed, and large-size single crystals were prepared by solid phase synthesis and top seed crystal method. It has three-dimensional channel structure and charge balance characteristics of Na+ and Cs+ filling, and is suitable for nonlinear optical devices. .
The obtained Li9Na3Cs2(SO4)7 nonlinear optical crystal has short UV absorption cut-off edge, moderate nonlinear optical effects and stable physical and chemical properties. It is suitable for the production of nonlinear optical devices and is suitable for military and civilian high-tech fields.
Smart Images

Figure CN115874284B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Li 9 Na 3 Cs 2 (SO 4 ) 7 Compounds, Li 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystals and Li 9 Na 3 Cs 2 (SO 4 ) 7 Crystals are used to make nonlinear optical devices. Technical Background
[0002] The nonlinear optical effect of a crystal refers to an effect in which the frequency of a laser beam with a certain polarization direction will change when it passes through a nonlinear optical crystal in a certain direction. Crystals with nonlinear optical effects are called nonlinear optical crystals. Using the nonlinear optical effect of crystals, nonlinear optical devices such as second harmonic generators, up / down frequency converters, and optical parametric oscillators can be made. All-solid-state lasers that use nonlinear optical crystals for frequency conversion are a future development direction for lasers, and the key lies in obtaining excellent nonlinear optical crystals.
[0003] At present, nonlinear optical crystals used in the ultraviolet band are all borates, mainly β-BaB 2 O 4 (BBO), LiB 3 O 5 (LBO), RbLiB 6 O 10 (CLBO) and K 2 Be 2 BO 3 F 2 (KBBF), etc., but they all have their own shortcomings. For example, CLBO is very easy to deliquesce and difficult to achieve commercial application; KBBF is difficult to obtain crystals with large c-direction thickness due to its severe layered growth habit. Therefore, it is still urgent and necessary to explore new ultraviolet nonlinear optical crystals with excellent comprehensive performance. Summary of the invention
[0004] One of the purposes of the present invention is to provide a 9 Na 3 Cs 2 (SO 4 ) 7 of compounds.
[0005] One of the purposes of the present invention is to provide a Li 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystals.
[0006] One of the purposes of the present invention is to provide a Li 9 Na 3 Cs 2 (SO 4 ) 7 Method for preparing nonlinear optical crystals.
[0007] One of the objects of the present invention is to provide Li 9 Na 3 Cs 2 (SO 4 ) 7 Uses of nonlinear optical crystals.
[0008] The technical solution of the present invention is as follows:
[0009] 1. A kind of Li 9 Na 3 Cs 2 (SO 4 ) 7 The compound, the Li 9 Na 3 Cs 2 (SO 4 ) 7 The chemical formula of the compound is Li 9 Na 3 Cs 2 (SO 4 ) 7 .
[0010] 2. The present invention provides a Li 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystal, the chemical formula of which is Li 9 Na 3 Cs 2 (SO 4 ) 7 , does not contain a symmetry center, belongs to the trigonal system, P3 space group, and the unit cell parameters are α=90°, β=90°, γ=120°, Z=3.
[0011] The basic structure of the crystal is composed of LiO4 Primitives and SO 4 The primitives are connected at the same vertices to form a three-dimensional channel structure. + and Cs + Filled in the pores to maintain charge balance. Powder frequency doubling test shows that the effective frequency doubling coefficient of the crystal is about 0.5 times that of the commercial nonlinear optical crystal KDP. The UV transmission spectrum shows that the UV absorption edge of the crystal is 160nm. The minimum deflection angle method test refractive index shows that the birefringence of the crystal in the light transmission band is 0.0046-0.0044.
[0012] 3. A kind of Li 9 Na 3 Cs 2 (SO 4 ) 7 A method for preparing a nonlinear optical crystal, wherein the Li 9 Na 3 Cs 2 (SO 4 ) 7 compounds, and obtained Li by top seeding method 9 Na 3 Cs 2 (SO 4 ) 7 The method comprises the following steps in sequence:
[0013] (1) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 Mix and grind evenly according to the stoichiometric ratio, put into a muffle furnace, and then heat to 500-600℃ at a rate of 10-200℃ / hour and sinter for 6-12 hours to obtain pure phase Li 9 Na 3 Cs 2 (SO 4 ) 7 Compounds;
[0014] (2) The pure phase Li obtained in step (1) 9 Na 3 Cs 2 (SO 4 ) 7 The compound is ground and placed in a crucible, and the temperature is raised to 695-705°C at a rate of 20-50°C / hour and kept at this temperature for 24-48 hours to obtain a uniform melt;
[0015] (3) Cooling the melt obtained in step (2) to 630-640°C, contacting the melt surface with a clean platinum wire, and slowly cooling the melt at a rate of 1-2°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystals are taken out of the liquid and cooled to room temperature at a rate of 5-8°C / hour to obtain the Li 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystals.
[0016] Furthermore, the method further comprises the following steps:
[0017] Take the obtained Li 9 Na 3 Cs 2 (SO 4 ) 7 The transparent and impurity-free part of the nonlinear optical crystal is used as a seed crystal, and then steps (1) and (2) are repeated to obtain a uniform melt, and then the melt is cooled to 630-640°C; the obtained seed crystal is contacted with the melt surface, and the melt is slowly cooled at a rate of 0.1-0.2°C / day until the crystal grows to an appropriate size, and then the crystal is taken out of the liquid surface and cooled to room temperature at a rate of 5-8°C / hour to obtain a large-sized Li 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystals.
[0018] The following are used to synthesize Li 9 Na 3 Cs 2 (SO 4 ) 7 Reactions of compounds:
[0019]
[0020] The Li of the present invention 9 Na 3 Cs 2 (SO 4 ) 7 The uses of nonlinear optical crystals include use as nonlinear optical devices.
[0021] Preferably, the Li 9 Na 3 Cs 2 (SO4 ) 7 The use of nonlinear optical crystals in the preparation of ultraviolet frequency-doubled laser output.
[0022] Preferably, the Li 9 Na 3 Cs 2 (SO 4 ) 7 The use of nonlinear optical crystals in the preparation of frequency doubling generators, up or down frequency converters or optical parametric oscillators.
[0023] Preferably, the nonlinear optical device prepared comprises passing at least one incident electromagnetic radiation through at least one Li 9 Na 3 Cs 2 (SO 4 ) 7 After the nonlinear optical crystal, a device that produces at least one beam of output radiation with a frequency different from the incident electromagnetic radiation.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) Obtained Li 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystals have the advantages of short ultraviolet absorption cutoff edge, moderate nonlinear optical effect, stable physical and chemical properties and good mechanical properties;
[0026] (2) The 9 Na 3 Cs 2 (SO 4 ) 7 Nonlinear optical crystals can be used to make nonlinear optical devices;
[0027] (3) The nonlinear optical devices made of the nonlinear optical crystal of the present invention can be used in a number of military and civilian high-tech fields, such as laser blinding weapons, optical disc recording, laser projection television, optical computing and optical fiber communication. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is to use Li 9 Na 3 Cs 2 (SO 4 ) 7 The working principle diagram of a typical nonlinear optical device made of crystal, where 1 is the laser, 2 is the incident laser beam, and 3 is the Li after crystal post-processing and optical processing. 9 Na3 Cs 2 (SO 4 ) 7 The crystal, 4 is the generated laser beam, and 5 is the filter.
[0029] Figure 2 Li of the present invention 9 Na 3 Cs 2 (SO 4 ) 7 X-ray diffraction patterns of polycrystalline powders and Cs-based 3 C 6 N 9 ·H 2 X-ray diffraction pattern of O single crystal structure simulation.
[0030] Figure 3 Li of the present invention 9 Na 3 Cs 2 (SO 4 ) 7 Crystal structure diagram.
[0031] Figure 4 Li obtained in Example 1 of the present invention 9 Na 3 Cs 2 (SO 4 ) 7 Centimeter-scale single crystals. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the embodiments and drawings. Those skilled in the art will appreciate that the following embodiments are not intended to limit the scope of protection of the present invention, and any improvements and changes made on the basis of the present invention are within the scope of protection of the present invention.
[0033] Examples 1-6 are about Li 9 Na 3 Cs 2 (SO 4 ) 7 Preparation of compounds.
[0034] Example 1
[0035] Solid phase synthesis of pure Li 9 Na 3 Cs 2 (SO 4 ) 7 , and the top seeding method was used to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7Large size single crystal. The specific operation is carried out in the following steps:
[0036] a) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 The mixture was mixed and ground evenly according to the stoichiometric ratio, placed in a muffle furnace, and then heated to 550°C at a rate of 50°C / hour and sintered for 12 hours to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Pure phase of a compound.
[0037] b) Li in step (a) 9 Na 3 Cs 2 (SO 4 ) 7 After the pure phase is ground, it is placed in a platinum crucible or a gold crucible, heated to 700°C at a rate of 20°C / hour and kept warm for 48 hours to obtain a uniform compound Li 9 Na 3 Cs 2 (SO 4 ) 7 of the melt.
[0038] c) cooling the melt obtained in step (b) to 640°C, contacting the melt surface with a clean platinum wire, and slowly cooling at a rate of 1°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystal was taken out of the liquid and cooled to room temperature at a rate of 5°C / hour to obtain the Li 9 Na 3 Cs 2 (SO 4 ) 7 Seed crystal for large-size single crystal growth.
[0039] d) Finally, the melt obtained by repeating steps (a) and (b) is cooled to 640°C, and the cut and polished seed crystal is fixed on the seed crystal rod with a platinum wire so that the seed crystal contacts the melt surface. The temperature is slowly lowered at a rate of 0.1°C / day until the crystal grows to an appropriate size. The crystal is taken out of the liquid surface and cooled to room temperature at a rate of 5°C / hour to obtain Li 9 Na 3 Cs 2 (SO 4 )7 Centimeter-scale single crystals.
[0040] Example 2
[0041] Solid phase synthesis of pure Li 9 Na 3 Cs 2 (SO 4 ) 7 , and the top seeding method was used to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Large size single crystal. The specific operation is carried out in the following steps:
[0042] a) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 Mix and grind evenly according to the stoichiometric ratio, put into a muffle furnace, and then heat to 500℃ at a rate of 10℃ / hour and sinter for 6 hours to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Pure phase of a compound.
[0043] b) Li in step (a) 9 Na 3 Cs 2 (SO 4 ) 7 After the pure phase is ground, it is placed in a platinum crucible or a gold crucible, heated to 700°C at a rate of 40°C / hour and kept warm for 24 hours to obtain a uniform compound Li 9 Na 3 Cs 2 (SO 4 ) 7 of the melt.
[0044] c) cooling the melt obtained in step (b) to 640°C, contacting the melt surface with a clean platinum wire, and slowly cooling at a rate of 2°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystal was taken out of the liquid and cooled to room temperature at a rate of 6°C / hour to obtain the Li 9 Na 3 Cs 2 (SO4 ) 7 Seed crystal for large-size single crystal growth.
[0045] d) Finally, the melt obtained by repeating steps (a) and (b) is cooled to 640°C, and the cut and polished seed crystal is fixed on the seed crystal rod with a platinum wire so that the seed crystal contacts the melt surface, and the temperature is slowly reduced at a rate of 0.15°C / day until the crystal grows to an appropriate size, and the crystal is taken out of the liquid surface and cooled to room temperature at a rate of 6°C / hour to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Centimeter-scale single crystals.
[0046] Example 3
[0047] Solid phase synthesis of pure Li 9 Na 3 Cs 2 (SO 4 ) 7 , and the top seeding method was used to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Large size single crystal. The specific operation is carried out in the following steps:
[0048] a) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 Mix and grind them evenly according to the stoichiometric ratio, put them into a muffle furnace, and then heat them to 600℃ at a rate of 200℃ / hour and sinter them for 12 hours to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Pure phase of a compound.
[0049] b) Li in step (a) 9 Na 3 Cs 2 (SO 4 ) 7 After the pure phase is ground, it is placed in a platinum crucible or a gold crucible, heated to 700°C at a rate of 50°C / hour and kept warm for 24 hours to obtain a uniform compound Li 9 Na 3 Cs 2 (SO 4 ) 7 of the melt.
[0050] c) cooling the melt obtained in step (b) to 640°C, contacting the melt surface with a clean platinum wire, and slowly cooling at a rate of 1.5°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystal was taken out of the liquid and cooled to room temperature at a rate of 7°C / hour to obtain the Li 9 Na 3 Cs 2 (SO 4 ) 7 Seed crystal for large-size single crystal growth.
[0051] d) Finally, the melt obtained by repeating steps (a) and (b) is cooled to 640°C, and the cut and polished seed crystal is fixed on the seed crystal rod with a platinum wire so that the seed crystal contacts the melt surface, and the temperature is slowly reduced at a rate of 0.2°C / day until the crystal grows to an appropriate size, and the crystal is taken out of the liquid surface and cooled to room temperature at a rate of 8°C / hour to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Centimeter-scale single crystals.
[0052] Example 4
[0053] Solid phase synthesis of pure Li 9 Na 3 Cs 2 (SO 4 ) 7 , and the top seeding method was used to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Large size single crystal. The specific operation is carried out in the following steps:
[0054] a) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 Mix and grind evenly according to the stoichiometric ratio, put into a muffle furnace, and then heat to 600℃ at a rate of 150℃ / hour and sinter for 12 hours to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Pure phase of a compound.
[0055] b) Li in step (a) 9 Na 3 Cs 2 (SO 4 ) 7 After the pure phase is ground, it is placed in a platinum crucible or a gold crucible, heated to 695°C at a rate of 50°C / hour and kept warm for 36 hours to obtain a uniform compound Li 9 Na 3 Cs 2 (SO 4 ) 7 of the melt.
[0056] c) cooling the melt obtained in step (b) to 640°C, contacting the melt surface with a clean platinum wire, and slowly cooling at a rate of 1.5°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystal was taken out of the liquid and cooled to room temperature at a rate of 8°C / hour to obtain the Li 9 Na 3 Cs 2 (SO 4 ) 7 Seed crystal for large-size single crystal growth.
[0057] d) Finally, the melt obtained by repeating steps (a) and (b) is cooled to 640°C, and the cut and polished seed crystal is fixed on the seed crystal rod with a platinum wire so that the seed crystal contacts the melt surface. The temperature is slowly lowered at a rate of 0.1°C / day until the crystal grows to an appropriate size. The crystal is taken out of the liquid surface and cooled to room temperature at a rate of 8°C / hour to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Centimeter-scale single crystals.
[0058] Example 5
[0059] Solid phase synthesis of pure Li 9 Na 3 Cs 2 (SO 4 ) 7 , and the top seeding method was used to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Large size single crystal. The specific operation is carried out in the following steps:
[0060] a) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 Mix and grind evenly according to the stoichiometric ratio, put into a muffle furnace, and then heat to 600℃ at a rate of 150℃ / hour and sinter for 12 hours to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Pure phase of a compound.
[0061] b) Li in step (a) 9 Na 3 Cs 2 (SO 4 ) 7 After the pure phase is ground, it is placed in a platinum crucible or a gold crucible, heated to 705°C at a rate of 50°C / hour and kept at this temperature for 48 hours to obtain a uniform compound Li 9 Na 3 Cs 2 (SO 4 ) 7 of the melt.
[0062] c) cooling the melt obtained in step (b) to 630°C, contacting the melt surface with a clean platinum wire, and slowly cooling at a rate of 1.5°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystal was taken out of the liquid and cooled to room temperature at a rate of 8°C / hour to obtain the Li 9 Na 3 Cs 2 (SO 4 ) 7 Seed crystal for large-size single crystal growth.
[0063] d) Finally, the melt obtained by repeating steps (a) and (b) is cooled to 630°C, and the cut and polished seed crystal is fixed on the seed crystal rod with a platinum wire so that the seed crystal contacts the melt surface, and the temperature is slowly reduced at a rate of 0.1°C / day until the crystal grows to an appropriate size, and the crystal is taken out of the liquid surface and cooled to room temperature at a rate of 8°C / hour to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Centimeter-scale single crystals.
[0064] Example 6
[0065] Solid phase synthesis of pure Li 9 Na 3 Cs 2 (SO 4 ) 7 , and the top seeding method was used to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Large size single crystal. The specific operation is carried out in the following steps:
[0066] a) First, Li 2 SO 4 、Na 2 SO 4 , Cs 2 SO 4 Mix and grind them evenly according to the stoichiometric ratio, put them into a muffle furnace, and then heat them to 600℃ at a rate of 150℃ / hour and sinter them for 8 hours to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Pure phase of a compound.
[0067] b) Li in step (a) 9 Na 3 Cs 2 (SO 4 ) 7 After the pure phase is ground, it is placed in a platinum crucible or a gold crucible, heated to 700°C at a rate of 20°C / hour and kept warm for 24 hours to obtain a uniform compound Li 9 Na 3 Cs 2 (SO 4 ) 7 of the melt.
[0068] c) cooling the melt obtained in step (b) to 635°C, contacting the melt surface with a clean platinum wire, and slowly cooling at a rate of 1°C / day until Li ions of appropriate size are precipitated on the platinum wire. 9 Na 3 Cs 2 (SO 4 ) 7 The crystal was taken out of the liquid and cooled to room temperature at a rate of 8°C / hour to obtain the Li 9 Na 3 Cs 2 (SO 4 ) 7Seed crystal for large-size single crystal growth.
[0069] d) Finally, the melt obtained by repeating steps (a) and (b) is cooled to 635°C, and the cut and polished seed crystal is fixed on the seed crystal rod with a platinum wire so that the seed crystal contacts the melt surface. The temperature is slowly lowered at a rate of 0.2°C / day until the crystal grows to an appropriate size. The crystal is taken out of the liquid surface and cooled to room temperature at a rate of 8°C / hour to obtain Li 9 Na 3 Cs 2 (SO 4 ) 7 Centimeter-scale single crystals.
[0070] The Li obtained in Example 1-6 9 Na 3 Cs 2 (SO 4 ) 7 The nonlinear optical crystal was tested for powder frequency doubling. The effective frequency doubling coefficient of the crystal at a wavelength of 1064nm was about 0.5 times that of the commercial nonlinear optical crystal KDP.
[0071] The Li obtained in Example 1-6 9 Na 3 Cs 2 (SO 4 ) 7 The nonlinear optical crystal was tested for transmission spectrum. The ultraviolet absorption cutoff edge of the crystal was about 160nm, and it was transmitted within the wavelength range of 160-1000nm.
[0072] Using the minimum deflection angle method to test Li 9 Na 3 Cs 2 (SO 4 ) 7 The refractive index of the crystal is 0.0046-0.0044 in the light transmission band.
[0073] Attached Figure 1 In order to use Li 9 Na 3 Cs 2 (SO 4 ) 7 A simple explanation of a nonlinear optical device made of crystal. A laser 1 emits a beam 2 that enters Li 9 Na 3 Cs 2 (SO 4 ) 7The output light beam 4 generated by the crystal 3 passes through the filter 5, thereby obtaining the required laser beam. The nonlinear optical laser can be a frequency doubling generator or an up / down frequency converter or an optical parametric oscillator, etc.
[0074] The above specific implementation methods are only detailed explanations of the technical solutions of the present invention. The present invention is not limited to the above embodiments. Those skilled in the art should understand that any improvements and substitutions based on the above principles and spirits on the basis of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a Li9Na3Cs2(SO4)7 nonlinear optical crystal, characterized in that: The specific steps include: (1) First, Li2SO4, Na2SO4, and Cs2SO4 are mixed and ground evenly according to a stoichiometric ratio, placed in a muffle furnace, and then heated to 500-600°C at a rate of 10-200°C / hour and sintered for 6-12 hours to obtain a pure phase Li9Na3Cs2(SO4)7 compound; (2) grinding the pure phase Li9Na3Cs2(SO4)7 compound obtained in step (1) and placing it in a crucible, heating it to 695-705°C at a rate of 20-50°C / hour and keeping it at that temperature for 24-48 hours to obtain a uniform melt; (3) cooling the melt obtained in step (2) to 630-640°C, contacting the melt surface with a clean platinum wire, slowly cooling the melt at a rate of 1-2°C / day until Li9Na3Cs2(SO4)7 crystals of appropriate size are precipitated on the platinum wire, taking the crystals out of the liquid surface, and cooling to room temperature at a rate of 5-8°C / hour, thereby obtaining the Li9Na3Cs2(SO4)7 nonlinear optical crystal; The transparent and impurity-free part of the obtained Li9Na3Cs2(SO4)7 nonlinear optical crystal is taken as a seed crystal, and then steps (1) and (2) are repeated to obtain a uniform melt, and then the melt is cooled to 630-640°C; the obtained seed crystal is contacted with the melt surface, and the melt is slowly cooled at a rate of 0.1-0.2°C / day until the crystal grows to an appropriate size, and then the crystal is taken out of the liquid surface and cooled to room temperature at a rate of 5-8°C / hour to obtain a large-sized Li9Na3Cs2(SO4)7 nonlinear optical crystal.
2. The use of the nonlinear optical crystal obtained by the method for preparing a Li9Na3Cs2(SO4)7 nonlinear optical crystal according to claim 1, characterized in that: The Li9Na3Cs2(SO4)7 nonlinear optical crystal is used as a nonlinear optical device.
3. A nonlinear optical device, characterized in that it is made of the Li9Na3Cs2(SO4)7 nonlinear optical crystal described in claim 1.